2010
DOI: 10.1208/s12249-010-9471-3
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of Microneedles Coated with Influenza Virus-like Particle Vaccine

Abstract: Abstract. Mortality due to seasonal and pandemic influenza could be reduced by increasing the speed of influenza vaccine production and distribution. We propose that vaccination can be expedited by (1) immunizing with influenza virus-like particle (VLP) vaccines, which are simpler and faster to manufacture than conventional egg-based inactivated virus vaccines, and (2) administering vaccines using microneedle patches, which should simplify vaccine distribution due to their small package size and possible self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(61 citation statements)
references
References 42 publications
(51 reference statements)
1
60
0
Order By: Relevance
“…Each MN array consisted of single rows of five microneedles (50 in total) with 700 m length, 200m width from the base and 50m thickness. Previous studies (Kim et al, 2010) have shown that coating of MNs requires proper design of coating formulations in order to achieve uniform coatings and avoid the creation of bulky layers. As shown in Table 2 the coating solutions composed of three anticancer agents, 5FU, CRC and CPT, with different water solubilities and the graft water soluble polymer Soluplus.…”
Section: Resultsmentioning
confidence: 99%
“…Each MN array consisted of single rows of five microneedles (50 in total) with 700 m length, 200m width from the base and 50m thickness. Previous studies (Kim et al, 2010) have shown that coating of MNs requires proper design of coating formulations in order to achieve uniform coatings and avoid the creation of bulky layers. As shown in Table 2 the coating solutions composed of three anticancer agents, 5FU, CRC and CPT, with different water solubilities and the graft water soluble polymer Soluplus.…”
Section: Resultsmentioning
confidence: 99%
“…Microneedle preparations and coatings were performed as described previously (27,30). Briefly, rows of solid metal microneedles were fabricated by cutting needle structures from stainless sheets (SS304, 75-m thickness; McMaster-Carr, Atlanta, GA) using an infrared laser (Resonetics Maestro, Nashua, NH), and the microneedles measured 700 m in length and 160 m in width.…”
Section: Methodsmentioning
confidence: 99%
“…The most common materials used for fabricating MN are metal, silicon and polymer (Zhao et al, 2006;Memon et al, 2011;Kim et al, 2012). The primary metals used for MNs are stainless steel (Martanto et al, 2004;Bal et al, 2008;Quan et al, 2010;Kim et al, 2012) and titanium (Parker et al, 2007;Fernandez et al, 2009;Kim et al, 2010). Metal MNs have the advantages of low cost, tougher hardness, ease of penetration into the tissue and they are not easily broken in the tissue.…”
Section: Gas Pressure and Particle Velocitymentioning
confidence: 99%